Handle with Care - Eric Daffron (Angles)
This essay examines two sets of coronavirus-prevention guidelines issued by New York City’s health department in early spring 2020. The department advised residents not to touch their faces “unless” they had washed their hands but advised them to masturbate “especially if” they had washed their hands. Those recommendations reshaped New Yorkers’ relationship to their bodies and, in so doing, contributed to a new permutation of biopower. Drawing on several theories of biopower, this essay’s first section explains that the department’s recommendations used large-scale biopolitical tactics with small-scale implications to encourage New Yorkers to meet the expectations of what Nikolas Rose has called “biological citizenship.” Exploring potential responses to the body’s biopolitical regulation, this essay’s second section considers the prohibition against touching in Sigmund Freud’s outdated but culturally resonant theory of obsessional neurosis. While obsessional neurosis may transgress, cancel, or achieve a compromise with that prohibition, only a ceremonial such as handwashing offers promise for responsible action. However, it, like the obsessional’s other actions, operates in a cycle of desire and prohibition which cannot fully account for how biopower now promotes and regulates bodily knowledge and movement. In search of alternatives, this essay’s final section turns to four coronavirus-themed pornographic videos produced by gay and bisexual men. These videos troubled public-health guidelines while providing potential viewers in New York and beyond with critical and creative options for pandemic-era action. In sum, these productions revealed that creation can come out of crisis.